The Relationship Between Personal Hygiene Knowledge and The Incidence of Luching in Women of Reproductive Age in Bumi Ratu Village Dusun 001-007 South Sungkai Regency North Lampung District in 2023 - Meilita, Masti; Mariza, Ana; Susilawati, Susilawati (Universitas Malahayati, 2023)
ABSTRACT Leucorrhoea is still a problem for women of childbearing age, where around 75% of women in the world experience vaginal discharge. Data in Indonesia states that the incidence of leucorrhoeahas reached 70%, in Lampung Province 2021, most cases of pathological leucorrhoea(67.7%) have been experienced. The impact of leucorrhoeathat is not treated can cause infertility and cancer. Factors that cause leucorrhoea include poor personal hygiene knowledge and behavior. Knowledge about personal hygiene is often ignored so that it can cause vaginal discharge. As much as 69.7% of women of childbearing age in Bumi Ratu Village experience leucorrhoeaand 80% do not know about personal hygiene. The purpose of this research is to know the correlation between personal hygiene knowledge and the incidence of leucorrhoea in reproductive women. The research method uses a quantitative research type, an analytic survey design with a cross-sectional time approach. The population in this study were all women of childbearing age in Bumi Ratu Village, 001-007, South Sungkai District, North Lampung Regency with a total sample of 164 people, using simple random sampling. Statistical test using the chi-square test. The statistical test results showed that most of the respondents had experienced pathological leucorrhoea(57.3%), and had poor knowledge about personal hygiene (51.2%). Statistical test results obtained p-value = 0.001, and OR = 3.034 . From the results of the study it can be concluded that there is a relationship between personal hygiene knowledge and the incidence of leucorrhoeain women of childbearing age. Suggestions for health workers in order to increase the knowledge of women of childbearing age about personal hygiene and leucorrhoeacan be done by providing health education about personal hygiene using interesting media. Keywords: Personal Hygiene, Leucorrhoea, Women of Reproductive